ESTÁGIO CURRICULAR NÃO-OBRIGATÓRIO: limites e perspectivas na formação dos estudantes para o mundo do trabalho - Pereira, Maria Rosane Soares (2011)
This work is an analysis of the optional internship as a way that allows the union between theory and practice. Has for its objective understand how this educational act helps with the formation and insert the students in the world of work. To materialize this objective, the research previously defined some paths that had the following guiding principles: the optional traineeship in the context of work and education , considering the changes that result from the flexible accumulation of the capitalist model of production; in this context became clear the innovations caused by the Traineeship Law n 11.788-2008 mainly related with the rights and the duties of the students. Still, the role of the education institutions , concessionaires Internship and the integration agents as essential components of this educational activity. The methodological path privileged the documental and field research. Analyze the study object from the dialect method e for its elaboration counted with the theoric luggage of important authors such as Marx, Gramsci, Boltanskyi e Chiapello, Mészaros, Antunes, Kuenzer, Pochmann, Santos, Oliveira, Reis. This research concluded that the optional traineeship is an articulator element between the education and the world of work, giving the students objectives conditions to know the profession they want, because allows the union of the theory with the practice in real environments of work, being essential to form the skills that are required from the public and private employers. Observed that for its right operation it is necessary the fulfillment of the Traineeship Law and others regulations that discipline it by the part of the social lead actors of this educational act.